Punya Prasad Regmi on the need to change people's mindsets on gender and climate change - CGIAR Research Program on Climate Change, Agriculture and Food Security (2013)
On October 2013, 22-25, the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) theme Linking Knowledge to Action coordinated a Gender Training and Strategizing Workshop, in Nairobi, Kenya. The ambition was to fast-track CCAFS partners and gender-enthusiasts from the five CCAFS regions, to take the lead on developing organisational strategies that will help them integrate gender into climate change and agriculture research. Read more about the workshop on our blog: http://ow.ly/qoF2w Learn more about the conference aim and get documents: http://ow.ly/qlVDi